2021
DOI: 10.1073/pnas.2104686118
|View full text |Cite
|
Sign up to set email alerts
|

Starvation induces shrinkage of the bacterial cytoplasm

Abstract: Environmental fluctuations are a common challenge for single-celled organisms; enteric bacteria such as Escherichia coli experience dramatic changes in nutrient availability, pH, and temperature during their journey into and out of the host. While the effects of altered nutrient availability on gene expression and protein synthesis are well known, their impacts on cytoplasmic dynamics and cell morphology have been largely overlooked. Here, we discover that depletion of utilizable nutrients results in shrinkage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 62 publications
5
47
0
Order By: Relevance
“…S19 and Movie S6 ), in agreement with previous reports ( 40 ). Plasmolysis was recently also reported upon complete starvation ( 41 ). Therefore, turgor depends on the nutrient-dependent energy state of the cell.…”
Section: Resultsmentioning
confidence: 94%
“…S19 and Movie S6 ), in agreement with previous reports ( 40 ). Plasmolysis was recently also reported upon complete starvation ( 41 ). Therefore, turgor depends on the nutrient-dependent energy state of the cell.…”
Section: Resultsmentioning
confidence: 94%
“…The nucleoid is thought to be a major contributor to the effective mesh size of the cytoplasm, and it has been shown in some bacterial species and conditions to compact during starvation (4). Cell volume in WT P. aeruginosa cells also decreases, which may contribute to overall crowding, and increased cytoplasmic density has been reported in E. coli under some starvation conditions (9). We have previously shown that ∆polyP cells fail to exit the cell cycle during nitrogen starvation, and therefore remain as large as WT growing cells (16).…”
Section: R a F Tmentioning
confidence: 80%
“…These changes are thought to be driven by decreased transcription and increased synthesis of starvation-specific nucleoid associated structural proteins (NAPs) (5)(6)(7)(8). Meanwhile, the cytoplasm exhibits an overall decrease in volume and increase in density in some bacteria as well as in yeast (9,10). In some cases, changes in the dynamics of cytoplasmic components have also been observed (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that cytosol shrinkage might be one of the results of cell starvation [ 40 ]. According to Shi and colleagues, the condensation of cytoplasm is a natural feature of cells experiencing nutrient depletion.…”
Section: Resultsmentioning
confidence: 99%